نظم معلومات الموارد البشرية و دورها في تحسين الآداء الوظيفي دراسة حالة بثانوية رزاق محمد الصغير عين سور سوق اهراس - سماح بوترعة; خديجة صيد (My University, 2022)
This studyaimed to highlight the impact end contribution that the humain resource information system can make with its three dimonsions: The devices and networks used ,programs and protection system ,as will as the skill of the humain resource to perform Humain resources througha case study, we carried out in the lycee rezegue mohamed sgere Ain senour, on a sample of 30 workers .The resultts of the studywere as follows -The device s and networks used in the human resources information system significantly affect the performance of workers . -The programs and protection systemsused in the Human resources Information System significantly affect the performance of workers -The programs and protection systemsused in the human resource wefind that it does not affect at all the performance of workers in the municipality. Finally ,we have made a number of propos als that wouldraise the level of human resource performance , perhaps the most important of whichis to encourage a culture of use human resources information system , itsdevelopment and continu ousupdating of its resources . ............................................................. هدفت هذه الدراسة الى ابراز الأثر و المساهمة التي يمكن ان يحدثها نظم معلومات الموارد البشرية بأبعاده الثلاثة المتمثلة في : الأجهزة و الشبكات المستعملة ،البرامج و أنظمة الحماية ، و كذلك مهارة المورد البشري على أداء الموارد البشرية من خلال دراسة الحالة التي قمنا بها في ثانوية رزاق محمد الصغير عين سينور على عينة من 30 عامل و كانت نتائج الدراسة كما يلي : -ان الأجهزة و الشبكات المستخدمة في نظم معلومات الموارد البشرية تؤثر بشكل ملحوظ على أداء العاملين -ان البرامج و أنظمة الحماية المستخدمة في نظم معلومات الموارد البشرية تؤثر بشكل ملحوظ على أداء العاملين -في حين ان البعد الثالث المتمثل في مهارة المورد البشري نجده لا يؤثر بتاتا على أداء العاملين بالثانوية و في الأخير قد قمنا بتقديم جملة من الاقتراحات من شأنها الرفع من مستوى المورد البشري و لعل من أهمها تشجيع ثقافة استخدام نظم معلومات الموارد البشرية و تطويره و تحديث موارده باستمرار